Notes on morphology and distribution of Acmanthera (A. Juss.) Griseb. (Malpighiaceae), an endemic genus from Brazil - Farroñay, Francisco; Perdiz, Ricardo De Oliveira; Prata, Eduardo Magalhães Borges; Vicentini, Alberto (Phytotaxa, 2019)
We present the amended description of the species Acmanthera minima and A. parviflora based on specimens collected in the Lower Negro River basin and the Serra do Aracá National Park, respectively, in the Amazonas State, Brazil. We also provide photographs, a distribution map, notes on conservation status and a key to all species of the genus Acmanthera. We report new records and range extension for Acmanthera latifolia and A. minima, previously known only for the Negro and Madeira River basins, respectively.